2022
DOI: 10.3390/cells11182907
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential (TRP) Channels in Airway Toxicity and Disease: An Update

Abstract: Our respiratory system is exposed to toxicants and pathogens from both sides: the airways and the vasculature. While tracheal, bronchial and alveolar epithelial cells form a natural barrier in the airways, endothelial cells protect the lung from perfused toxic compounds, particulate matter and invading microorganism in the vascular system. Damages induce inflammation by our immune response and wound healing by (myo)fibroblast proliferation. Members of the transient receptor potential (TRP) superfamily of ion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 176 publications
0
6
0
Order By: Relevance
“…In the respiratory tract, a series of ion channels are expressed in airway cells and control the balance of intracellular Ca 2+ and extracellular Ca 2+ concentrations. Abnormal ion channel switching ultimately activates the pathogenesis of asthma (Valverde et al 2011 ; Muller, et al 2022 ). The exploration of participating ion channels revealed that L-VDLCCs, NSCCs, NCXs and potassium channels were regulated and that the channel currents were altered during the process of PP121-induced relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…In the respiratory tract, a series of ion channels are expressed in airway cells and control the balance of intracellular Ca 2+ and extracellular Ca 2+ concentrations. Abnormal ion channel switching ultimately activates the pathogenesis of asthma (Valverde et al 2011 ; Muller, et al 2022 ). The exploration of participating ion channels revealed that L-VDLCCs, NSCCs, NCXs and potassium channels were regulated and that the channel currents were altered during the process of PP121-induced relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical studies involving respiratory disease models, GDC-0334 exhibited inhibition toward edema formation, smooth muscle hyperreactivity, and cough response. 72 , 73 Drug discovery strategies have been challenged owing to the limited bioavailability of TRPA1 antagonists.…”
Section: Trpa1 As a Drug Targetmentioning
confidence: 99%
“…Transient receptor potential channels are non-selective Ca +2 channels involved in a plethora of pathological and physiological roles [ 17 , 18 , 19 , 20 , 21 ]. First described in Drosophila melanogaster (for review see: [ 22 , 23 , 24 ]), it is now known that their expressions and activation profiles on neuronal and non-neuronal cells can influence the protection against or the development of a range of chronic diseases in mammals, including pain [ 25 , 26 ], cardiovascular diseases [ 27 , 28 ], asthma [ 29 , 30 ], amongst others. Also, their contributions to MS have been explored within the last several decades, especially in regard to TRP vanilloid 1 (TRPV1) and TRP ankyrin 1 (TRPA1) channels [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%